Optimal Utilization of Combined Double Layer and Nernstian Charging of Activated Carbon Electrodes in Aqueous Halide Supercapattery through Capacitance Unequalization. Issue 16 (1st January 2018) - Akinwolemiwa, Bamidele; Wei, Chaohui; Yang, Qinghua; Yu, Linpo; Xia, Lan; Hu, Di; Peng, Chuang; Chen, George Z.
Abstract : Charge storage through electric double layer (EDL) charging of activated carbon (AC) and redox reactions of iodide and bromide ions in aqueous electrolytes and at the AC | electrolyte interface has been investigated by cyclic voltammetry and galvanostatic charging and discharging. Electrochemical experiments were carried out in both the three-electrode and two-electrode cells with the latter resembling the so-called supercapacitor-battery hybrid or simply supercapattery. By comparing the electrochemical behavior of bromide and iodide ions used as dissolved redox species (DRS), some observed features of the supercapattery are described and analyzed from the standpoint of the EDL charging of the AC electrodes, the thermodynamics and kinetics of the electrode reactions of the DRS, and the adsorption and transport of the charging reaction products. Furthermore, the effect of capacitance unequalization was explored for the adequate utilization of the charge storage from both the DRS and EDL contributions. It is also shown that counter-electrode oversizing has to be critically appraised for the design of optimal devices.